Assessment of the vulnerability of a coastal freshwater system to climatic and non-climatic changes: A system dynamics approach. (10th May 2018) - Phan, Thuc D.; Smart, James C.R.; Sahin, Oz; Capon, Samantha J.; Hadwen, Wade L.
Abstract: Water resources management faces many challenges in coastal areas of developing countries, where climate change coupled with high rates of population growth and urbanization have the potential to cause severe water scarcity. Of particular concern, are sea level rise and altered precipitation regimes that will influence spatial and temporal patterns of river discharge, water levels and saltwater penetration in estuaries. A sound understanding of factors affecting the vulnerability of coastal freshwater systems is therefore needed to mitigate the potential impacts of climatic and non-climatic changes. In this study, a system dynamics modeling approach was employed to explore the vulnerability of the coastal freshwater system in Da Do Basin, Vietnam to projected sea level rise, upstream flow decline and socio-economic development. This system includes the Da Do River and irrigation channels that receive freshwater through sluice gates from the Van Uc and Lach Tray rivers. The model was developed as a learning tool for decision-makers to improve their understanding of the spatial and temporal dynamic behaviors of the system and to inform adaptation decision-making by allowing exploration of plausible future scenarios. The model was developed, calibrated and validated using both historical data and expert knowledge elucidated via stakeholder consultation. Model results indicate that under current conditions, freshwater availability is sufficient to meet existing domestic, industrial and agricultural demands. However, the coastal freshwater system changes significantly and collapses under several plausible future scenarios. Future projections suggest that declining upstream flows will be the strongest threat to the system's vulnerability. System dynamics models enable consideration of the interactive effects of a range of climatic and non-climatic drivers on water resources availability thereby facilitating improved planning for collective and proactive adaptation actions to efficiently secure freshwater resources to support socio-economic development of coastal basins in the face of climate change. Highlights: Coastal freshwater systems are driven by climatic and non-climatic feedback processes. Coupled biophysical, hydrological and socio-economic feedback processes are simulated. The freshwater system changes significantly or collapses under some future scenarios. Declined upstream flows is the biggest threat to the system's future operation. Sluice gates in the system's lower reaches is closed under climate change scenarios.